Особливості розвитку стресостійкості майбутніх психологів методами гештальт-терапії - Овчиннікова, Ольга; Підбуцька, Ніна Вікторівна (Національний технічний університет "Харківський політехнічний інститут", 2023)
У статті проаналізовано наукову літературу присвячену темі стресостійкості. Схематично представлено процес впливу факторів стресу на людину. Наглядно проілюстровано місце реакцій організму на вплив стресорів у процесі розвитку стресостійкості. Дано власне визначення поняттю стресостійкість. Виділено основні складові стресостійкості. Обґрунтовано необхідність розвитку стресостійкості майбутніх психологів. Висвітлено значущість використання методів гештальт-терапії у процесі розвитку стресостійкості майбутніх психологів.

This article is devoted to analyze the scientific literature on the topic of stress resistance. It is schematically presented the process of impact of stress factors on a person. This paper clearly illustrates the role of the body's reactions to stressors in the development of stress resistance. The article gives the own concept of stress resistance. It is highlighted the main components of stress resistance. This article substantiates the need to develop stress resistance of future psychologists. It is underlined the significance of the use of Gestalt therapy methods in the process of developing stress resistance of future psychologists.
Development of stress resistance of future psychologists using gestalt therapy methods
Keywords: стрес; стресор; вплив; стресостікість; складові стресостійкості; розвиток; майбутні психологи; метод; гештальт-терапія; stress; stressor; impact; stress resistance; components of stress resistance; development; future psychologists; method; Gestalt therapy